Perception of healthy eating among romanian adults - Cînpeanu, Oona-Cristina (2019)
Background: Totaling about 60% of all causes of death, chronic illnesses are the main cause of global mortality. Unhealthy behaviors, such as unbalanced eating or insufficient physical activity, can trigger metabolic changes, manifested by hypertension, high blood sugar, hyperlipidemia, obesity. These changes are grouped into the category of metabolic risk factors. Over time, these factors can cause cardiovascular diseases associated with a high mortality rate. Aim of the study: To evaluate the perception of healthy eating in a Romanian population. Material and methods: We applied a validated online questionnaire aimed to investigate people’s attitude towards diet and their motivation regarding food consumption in ten countries, based on an international project. For the present paper, we evaluated a Romanian sample of 821 adult respondents. Results: Most of the subjects (82.82%) were from an urban area, and 68.94% were women. Regarding the prevalence of chronic diseases, 3.53% of participants had cardiovascular disease, 6.69% had high cholesterol levels, 7.18% were obese, and 6.57% were suffering from high blood pressure. Significant correlations have been identified between calorie count, excessive sugar and salt consumption, gender variables, cardiovascular disease, obesity, and high blood pressure. Also, tradition is very important in relation to eating behaviors, being highly correlated with obesity. The general direction of answers was correct, even if half of the questionnaire items were formulated in a ‘negative’ way, and disagreement is needed for a consistent response with a correct perception of healthy diets. The overall perception of healthy eating was consistent with scientific information in the field. Conclusion: Women are generally better informed than men regarding healthy eating. Also, there is a possible conflict between traditional food-related cultural values and modern nutritional guidelines based on scientific information.